A Rational Solutions to the Crisis of Religious Understanding According to Ibn Rushd's Thought - Herliyanto; Maspuroh; Dela Amalliyah (Al-Iffah: Journal of Islamic Sciences Research, 2025)
This article discusses the philosophical thought of Ibn Rushd, a prominent Islamic philosopher of the 12th century. The discussion begins with his biography, detailing his intellectual journey and contributions to various fields, including philosophy, theology, and medicine. Ibn Rushd is best known for his commentaries on Aristotle, which significantly influenced both Islamic and Western philosophical traditions. His major works, such as Tahafut al-Tahafut (The Incoherence of the Incoherence) and Fasl al-Maqal, demonstrate his commitment to rationalism and the reconciliation of reason with faith. This article aims to explore the depth of Ibn Rushd’s philosophy, his impact on the Islamic world, and his lasting influence on European thought.